Economic development and environmental history in the Anthropocene perspectives on Asia and Africa - Austin, Gareth ([Bloomsbury Academic], 2019)
"For the populations of the developing economies - the vast majority of humanity - the present century offers the prospect of emulating Western standards of living. This hope is combined with increasing awareness of the environmental consequences of the very process of global industrialisation itself. This book explores the interactions between economic development and the physical environment in four regions of the developing world: Sub-Saharan Africa, South Asia, Southeast Asia and East Asia. The contributors focus on the 'Anthropocene': our present era, in which humanity's influence on the physical environment has begun to mark the geological record.